A new program to 13C NMR spectrum prediction based on tridimensional models. Issue 2 (2001) - Magri Magri, Fátima M. M. Fátima M. M.; Militão Militão, Júlio S. L. Júlio S. L.; Ferreira Ferreira, Marcelo J. P. Marcelo J. P.; Brant Brant, Antônio J. C. Antônio J. C.; Emerenciano Emerenciano, Vicente P. Vicente P.
Abstract : This work describes a new program creation, written for Windows environment for 13 C NMR spectrum prediction based on interatomic distances and types of atoms. It has shown to be more efficient on forecast of natural product spectra than some commercial programs such as ACD and DENDRAL. Predictions of spectra of molecules with great conformational variations, as, for example, sesquiterpene lactones, are given.